Socialcar
Project
Sign in
Ask The Question
English
French
Spanish
Portuguese
Polish
Romanian
Mathematics
kimberstarr3
Jul 14, 2018, 1:21:30 PM
28
Removing the bracket then factorize 3(x-5)+4(x-2) ?
+2
(
1
) Answers
FarahBarnthouse209
Jul 14, 2018, 8:58:08 PM
3x -15+ 4x-8= 3x + 4x -15 -8= x(3+4) -23= 7x-23
Add answer
Sign in
Sign up
Related Questions
Removing the bracket then factorize 3(x-5)+4(x-2) ?
factorize x^3+4x^2+x-6
What's x^4-7x^2+1 ( factorize step-by-step)
factorize the following: 5(3a+3)+2(6a+5)
Which one of the following equations illustrates the commutative property? 8 + 3 = 4 + 7 If 3 + 5...
Factorize 8x²+10x-12 = ??? Juste tell me if(4x-3) (x+2) is the right answer please.
Simplify. Consider all the cases. Example: x−5= x−5, if x>5 0, if x=5 5−x, if x<5 2x+...
if x > 0, then the expression ((x^3)^-2)^5 is equivalent to
PLEASE HELP!! Factor out the GCF of three terms, then complete the factorization of 6x^3 + 6x^2 ...
2x + 3xy + 4 - x (y + 3) Simplify, then evaluate. x=5 and y=2